Część zamiast całości czyli sposób na cenzorów. "Szkoła podstawowa" Tomasza Zygadły – wzorcowy film kina „nowej zmiany” - Jazdon, Mikołaj (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2014)
Mikołaj Jazdon in his article presents an analysis and interpretation of a documentary that became a “trademark” of the young generation’s cinema from the decade of the Cinema of Moral Anxiety in Poland. Zygadło filmed the social behaviour of students in a Warsaw primary school to depict the fatal influence of the communist system on Polish youth, who were encouraged to tattle on each other. The method of portraying a social group from one place, as in Zygadłos Primary School, became popular among other documentary filmmakers from his generation. They began to shoot films about institutions like factories, schools or hospitals, focusing on the social relations between the people working there. These films were intentionally made as metaphors of Poland in the 1970s and of the rules operating in a country ruled by the Communist Party. The auteur strategy of depicting reality in a “pars pro toto” manner allowed documentary filmmakers to outwit the Party censors.